Some-where over the rainbow - Lucia Saks (Communicare)
"Nowadays, a far graver mistake is made: race is confused with nation and a sovereignty analogous to that of really existing peoples is attributed to ethnographic or. rather linguistic groups. " Ernest Renan.18821 Although Jacques Derrida is not usually thought of in terms of the problematics of nations and nationalism, the term "endless deferral" cannot help but evoke his philosophical project, and it is to his picture of logo centrism that I initially tum in elaborating ,South Africa's "preeminent" status as a nation whose identity always seems to reside in some "elsewhere" space. Apartheid may well be considered as the last 10- geocentric colonial structure (unless, that is, one wishes to included Bosnia under this unpleasant rubric) to finally collapse.1 Further its collapse may be considered the end of a state apparatus formed as an institutionalization of logocentric thinking (something unusual for Derrida who very rarely talks in terms of practices). Let me then begin this paper by turning to the idea of logo centrism and slowly proceed through it to the theme of national identity and its deployment by various theorists.